Supporting and scaffolding your students in (Post) Corona-times: Some practical ideas and strategies inspired by research - Mullamaa, Kristina (Archives of Business Research, 2020)
Student and teacher cooperation have long been considered to be the pillars of a meaningful learning process. In the article below we view some aspects of motivating students and empowering teachers that may be relevant for a balanced study process in such cooperation.